Idealisme: Pandangan tentang Hakikat Realitas dan Nilai, Bagaimana Idealisme Memengaruhi Tujuan Pendidikan Kristen (Menjadi Serupa dengan Allah) - Marny Touh; Renya A. Pandie; Margarita Tenis; Egisius Taneo; Ledi K. Ellu; Ireni Irnawati Pellokila (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2026)
Idealism has made a significant contribution to the development of modern education, particularly in shaping curricula, learning orientations, and the reinforcement of moral values that foster students’ character formation. The shift in educational paradigms that increasingly emphasizes intellectual and ethical dimensions demonstrates the relevance of idealist thought as a philosophical foundation that views reality as grounded in ideas, concepts, and rational consciousness. This study addresses the question of how the essence of idealism is philosophically understood and how its implications extend to religion, economics, politics, and education as spheres of human praxis. The research employs a literature review method through critical analysis of various scholarly articles discussing idealism as a philosophical school of thought and its contemporary relevance. The findings indicate that idealism posits ideas as the fundamental reality, while matter is understood as the outward manifestation of deeper inner dimensions such as mind, soul, and values. This perspective affirms that education should not merely focus on material and pragmatic aspects, but rather on the formation of character, morality, and spiritual awareness. The novelty of this study lies in its comprehensive synthesis between the metaphysical concepts of idealism and their multidimensional application in religion, economics, politics, and education, thereby offering an integrative perspective that underscores the urgency of ideal values in building a civilization grounded in thought and ethics.